Análise da diversidade sexual e da inclusão na campanha "Viva a liberdade de ser quem você é", de Doritos® Rainbow - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The research was guided by the following question: How is sexual diversity represented in the “Live the freedom of being who you are” campaign by Doritos® Rainbow? The general objective was to examine how sexual diversity is represented in the Doritos® Rainbow campaign “Live the freedom of being who you are.” Specifically, the study aimed to: identify which elements of the “Live your freedom” campaign are associated with sexual diversity; determine which of these elements are related to inclusion; and analyze how sexual diversity is addressed in the campaign to engage and raise awareness in the target audience. This is an exploratory, qualitative study, employing content analysis to interpret the campaign’s visual data. As for the results, the study found that the campaign uses audience segmentation and emotional appeal as key strategies tied to diversity and social inclusion. The campaign is primarily aimed at the LGBTQIAPN+ community and addresses themes such as sexual diversity, gender performativity, the subversion of heteronormative and cisnormative standards, intersectionality, and cultural representation. Through symbolic and visual elements — such as the colors of the LGBTQIAPN+ flag and the inclusion of people who reflect this diversity — the campaign seeks to engage and represent its target audience. It is concluded that sexual diversity in the Doritos® Rainbow campaign is represented by real, plural, and intersectional LGBTQIAPN+ individuals, with an emphasis on the appreciation of differences, the use of affirmative aesthetics, and a political discourse of inclusion and empowerment. In this way, the campaign turns advertising into an act of visibility and resistance, promoting not only a product but also a social cause.
Analysis of sexual diversity and inclusion in the Doritos® Rainbow campaign "Live the freedom to be who you are"
Keywords: Diversidade sexual; Publicidade; Comunicação Social; Inclusão Social; Sexual diversity; Advertising; Social Communication; Social Inclusion; CIENCIAS SOCIAIS APLICADAS